Glycosylated Natural Products From Marine Microbes - Li, Kunlong; Cai, Jian; Su, Ziqi; Yang, Bin; Liu, Yonghong; Zhou, Xuefeng; Huang, Jingxia; Tao, Huaming (Frontiers in Chemistry, 2020)
A growing body of evidence indicates that glycosylated natural products have become vital platforms for the development of many existing first-line drugs. This review covers 205 new glycosides over the last 22 years (1997–2018), from marine microbes, including bacteria, cyanobacteria and fungi. Herein, we discuss the structures and biological activities of these compounds, as well as the details of their source organisms.